2011
DOI: 10.1007/s00401-010-0795-6
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil (Viagra) ameliorates clinical symptoms and neuropathology in a mouse model of multiple sclerosis

Abstract: Cyclic GMP (cGMP)-mediated pathways regulate inflammatory responses in immune and CNS cells. Recently, cGMP phosphodiesterase inhibitors such as sildenafil, commonly used to treat sexual dysfunction in humans including multiple sclerosis (MS) patients, have been reported to be neuroprotective in animal models of stroke, Alzheimer's disease, and focal brain lesion. In this work, we have examined if sildenafil ameliorates myelin oligodendrocyte glycoprotein peptide (MOG₃₅₋₅₅)-induced experimental autoimmune ence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 39 publications
3
52
0
Order By: Relevance
“…As above mentioned, sildenafil treatment after cuprizone induced demyelination preserved myelin and axon integrity (Nunes et al 2012, Raposo et al 2014) and previous studies developed in the laboratory where this thesis was developed have shown in significant amelioration of EAE clinical symptoms after sildenafil treatment, suggesting a possible role of sildenafil in remyelination due to an increase in myelin stainings the protection exerted against apoptotic death of oligodendrocytes, the decrease of reactive gliosis and increase in neurotrophic factor BDNF (Pifarre et al 2011, Pifarre et al 2014). …”
Section: Cgmp and Remyelinationmentioning
confidence: 63%
See 4 more Smart Citations
“…As above mentioned, sildenafil treatment after cuprizone induced demyelination preserved myelin and axon integrity (Nunes et al 2012, Raposo et al 2014) and previous studies developed in the laboratory where this thesis was developed have shown in significant amelioration of EAE clinical symptoms after sildenafil treatment, suggesting a possible role of sildenafil in remyelination due to an increase in myelin stainings the protection exerted against apoptotic death of oligodendrocytes, the decrease of reactive gliosis and increase in neurotrophic factor BDNF (Pifarre et al 2011, Pifarre et al 2014). …”
Section: Cgmp and Remyelinationmentioning
confidence: 63%
“…Studies conducted in the laboratory where this thesis was developed showed that in a model of multiple sclerosis (MS), MOG induced experimental autoimmune encephalomyelitis (EAE), that the administration of the PDE5 inhibitor sildenafil in the acute phase of the disease rapidly ameliorates clinical symptoms, prevents axonal, decreased CD3+-leukocyte infiltration and microglial/macrophage activation in the spinal cord and suggests to restore myelin content (Pifarre et al 2011). Additionally, early administration of sildenafil have shown to delay EAE progression, preserves axons and myelin sheath integrity, prevents the death of oligodendrocytes and enhances expression of BDNF neurotrofic factor in chronic EAE, it was also observed reduced microglia/macrophage reactivity while increased the expression of Ym-1 anti-inflammatory microglia/macrophage phenotype (M2) protein and modulating adaptative immune response (Pifarre et al 2014).…”
Section: Aimsmentioning
confidence: 99%
See 3 more Smart Citations